Multi-route method of work organization for transport vehicles - Sergei A. Azemsha (Вестник СибАДИ)
Introduction. The degree of passenger capacity and operating time of route vehicles’ utilization determine the work efficiency of regular passenger transport. Therefore, the development of measures to increase the effectiveness rate of passenger load factor use of route vehicles, to reduce its unproductive downtime is relevant to fasten the payback period of regular passenger transport and allows to enhance the efficiency of its operation.The reason for low passenger load factor utilization of the route vehicles and high values of its inefficient downtime is the unevenness of passenger flow. The existing route-by-route method of work organization consists in the fact that vehicles go out on the line to one route. Its number, capacity, movement interval depend on peak values of passenger flow. During off-peak times, periods of on-duty traffic, the quantity of passengers decreases sharply, which leads to the declining in the degree of route vehicles’ capacity utilization. To ensure the acceptable values of this passenger load factor use, transportation operators increase the traffic interval by extension of unproductive downtime duration at the end points, which affects negatively the efficiency of regular passenger transport.The aim of the research is to develop a new method of organizing the work of route vehicles, which allows to increase the efficiency of regular passenger transport.Materials and Methods. Methods of analysis and generalization of literary sources, the principles of graph theory, formalization and mathematical formulation of the objective function and constraints were used while writing.Conclusions. A multi-route method of the work planning of route vehicles is proposed, which consists in the optimal distribution of trips of all routes of the considered route network between the fleet of available route vehicles, allowing to reduce its unproductive downtime and to increase the effectiveness rate of passenger load capacity utilization due to the possibility of route vehicles’ use on different routes, which will decrease the cost of such trips.For optimal distribution of trips of all routes of the considered route network between the fleet of available route vehicles, such trips are represented as vertices of the attributed graph, and possible activities between trips (idle time, empty runs) – as arcs. The set of vertices and arcs of such a graph represent cycles, each of which is a set of trips to be performed by a route vehicle during the operation time. In order to select a set of cycles, providing minimum costs for the carrying out all trips, the corresponding objective function was formulated. To ensure conditions objectively existing for route vehicles operation, a number of constraints were imposed on the objective function.Potential Application of Research Results. The results obtained represent an objective function and constraints that enable the implementation of a multi-route method for organizing public transport vehicles’ operation. Results can be applied to a city’s transport network to improve the efficiency of regular public transport services by reducing operational costs without deterioration in the quality of the provided services for the passengers.Practical Significance. The proposed multi-route method of work operation of regular public transport vehicles allows to shorten the operating costs by increasing the effectiveness rate of passenger load factor use and reducing unproductive idle times. This method does not diminish passenger service quality as it does not involve canceling trips and (or) prolongation of the intervals between vehicle routes.Originality in academic context. This work presents a novel method for organizing the operation of public transport vehicles, which helps to cut the operational costs without compromising the service quality. The article will be useful for public transport governing officials responsible for organizing urban regular public transport, as well as employees of urban public transport enterprises and transport industry researchers.